Pengaruh perlakuan benih tomat dengan pseudomonas putida pf-20 terhadap penyakit layu bakteri(ralstonia solanacearum)=The Influence of Tomato Seeds Treatment with Pseudomonas utida Pf-20 against Bacterial Wilt Disease... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Pseudomonas putida was one of antagonist bacteria employed on plant seed treatment to control the pathogens from soil carrying. The antagonist bacteria coated around seeds (seedcoating) were rapidly to colonize and spread through root stem when the seeds had germinated and had grown roots into soil. Therefore, the pathogens will difficulty penetrate the plant since antagonist bacteria had dominated the root stem environment. The seed treatment might be undertaken with both soil carrier material based and 1% arabic gum adhesive material based dry formulations. This research was aimed to verify the effectiveness of the compost soil dry formulation invested by P. putida (Pf-20) bacteria and subsequently coated around the tomato seeds to control bacterial drooping disease. The seed treatments verified were the non-coated pure seeds as the controlling ones (A), the non-antagonist bacteria seedcoating (B), the Pf-20 Wildtype seedcoating (C), and the seedcoating with Pf-20 Na/Rz/mutant'(D). The result showed that either the Pf-20 Wildtype bacteria or the Pf-20 NalRif mutant coated around the tomato were able to decrease the bacteria drooping disease rather than the controlling seeds or the non-antagonist bacterial seedcoating.